2015
DOI: 10.1109/tasc.2014.2365109
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling and Experimental Analysis of AC Critical Current in YBCO-Coated Conductors

Abstract: Critical current is generally defined by the dc measurement at which current produces voltage of E c = 10 −4 Vm −1 . However, most applications of superconductor are operating at alternating current (ac). Moreover, the ac current-carrying capability of superconductor has attracted extensive attention. This paper is aimed to define the transport ac critical current and put forward a novel electric field criterion based on numerical modeling and experimental analysis. YBCO-coated conductor is investigated becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Considering the H-formulation, the previous works dedicated to the validation of the model only contrasted the calculated results with measurements provided by a mean value of the current distribution, which represents an indirect comparison. Generally, the results are presented with good agreement [4,[13][14][15][16] for the energy dissipated (power losses) in a superconducting tape transporting an AC current. Also, the Hformulation by FEM simulations was successfully compared with levitation force measurements [17].…”
Section: Comsolmentioning
confidence: 74%
“…Considering the H-formulation, the previous works dedicated to the validation of the model only contrasted the calculated results with measurements provided by a mean value of the current distribution, which represents an indirect comparison. Generally, the results are presented with good agreement [4,[13][14][15][16] for the energy dissipated (power losses) in a superconducting tape transporting an AC current. Also, the Hformulation by FEM simulations was successfully compared with levitation force measurements [17].…”
Section: Comsolmentioning
confidence: 74%
“…It has been previously reported that the measured I-V characteristics of HTS tapes are sensitive to the rate at which current is injected into the material [112][113][114][115] in both thin film and cylindrical wire geometries. In that work an analytic model has been presented in which the electric field in the edge regions can be several orders of magnitude larger than at the tape centre.…”
Section: Fe Modelling Of I Cs At Different Ramp Ratesmentioning
confidence: 99%